THE RESPONSIBILITY OF TRANSNATIONAL CORPORATIONS FOR HUMAN RIGHTS VIOLATION:: CASE STUDY ON WORK IN SIMILAR CONDITIONS TO SLAVERY IN THE TEXTILE INDUSTRY (Revista Direitos Humanos e Democracia, 2021)
As a result of the rise of wealth and economic power of large corporations, which have come to represent as new actors in the international community, there is a need for the law to ensure that the relations arising from this perspective are regulated according to the precepts disseminated in the international community. One of the main obstacles faced in this perspective is the control and repression of acts of human rights violations practiced by transnational corporations, and the purpose of this article is to analyze this problem. In order to answer the following question: what means exist to reduce and/or eliminate human rights violations by the transnational textile industry, it was necessary to study and analyze effective legal instruments for national and international control of the actions of these new actors, so that the acts of human rights violations perpetrated by these companies are adequately prevented and remedied. In order to perform this study, the hypothetical-deductive method was used, and the textile industry was selected as a way of making the analysis of the existing control instruments more accurate.